2012
DOI: 10.1097/ico.0b013e3182151e0e
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Subconjunctival Bevacizumab Injection in Impending Recurrent Pterygium: A Pilot Study

Abstract: A single subconjunctival bevacizumab injection seems to only partially and transiently decrease conjunctival vascularization in impending recurrent pterygium in a dose-dependent manner. This treatment does not cause regression or reduce the recurrent rate of impending recurrent pterygium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 22 publications
2
31
0
2
Order By: Relevance
“…[59][60][61] Although VEGF receptor activation induces responses through TRPV1 transactivation, there are many studies indicating that antineovascularizing agents, such as bevacizumab, are ineffective in preventing recurrence of pterygial outgrowths after surgery. [62][63][64][65] In many cases, if it is at all effective, it only delays recurrence. 62,66 This limitation may be due to the short half-life of anti-VEGF agents at the ocular surface and to the difficulty in determining the ideal dose and treatment regimen to prevent pterygia over an extended period.…”
Section: Limitations Of Current Therapeutic Optionsmentioning
confidence: 99%
“…[59][60][61] Although VEGF receptor activation induces responses through TRPV1 transactivation, there are many studies indicating that antineovascularizing agents, such as bevacizumab, are ineffective in preventing recurrence of pterygial outgrowths after surgery. [62][63][64][65] In many cases, if it is at all effective, it only delays recurrence. 62,66 This limitation may be due to the short half-life of anti-VEGF agents at the ocular surface and to the difficulty in determining the ideal dose and treatment regimen to prevent pterygia over an extended period.…”
Section: Limitations Of Current Therapeutic Optionsmentioning
confidence: 99%
“…These include steroids to reduce inflammation and scarring, 8 peri-operative application of antimetabolites such as mitomycin C (MMC) 9 or 5 fluorouracil (5FU), 10,11 and, more recently, the use of anti-VEGF antibodies administered topically or subconjunctivally. 12,13 Other previously adopted techniques such as beta radiation have been abandoned because of the high risk for scleral melt. 14 5FU is a pyrimidine analogue that interferes with DNA and RNA synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…One of our previous studies concerning the presence and distribution of thymine dimers inside pterygium epithelium showed that basal cells are characterized by the highest expression of thymine dimers, which was also associated with a high density of p53 mutant basal cells [20]. Studies performed on UVB-induced thymine-thymine dimers in skin lesions revealed that the formation of thymine dimers is followed by an up-regulation of cyclooxygenase-2 expression and, subsequently, vascular endothelial growth factor overexpression [21]. Also, several papers reported that p53 promotes VEGF expression most probably by inducing VEGF transcription upon hypoxia exposure by binding, in an HIF-1α-dependent manner, to a highly conserved and functional p53-binding site within the VEGF promoter [22,23,24,25].…”
Section: Discussionmentioning
confidence: 99%